2020
DOI: 10.3389/fnagi.2020.594571
|View full text |Cite
|
Sign up to set email alerts
|

LncRNAs Stand as Potent Biomarkers and Therapeutic Targets for Stroke

Abstract: Stroke is a major public health problem worldwide with a high burden of neurological disability and mortality. Long noncoding RNAs (lncRNAs) have attracted much attention in the past decades because of their newly discovered roles in pathophysiological processes in many diseases. The abundance of lncRNAs in the nervous system indicates that they may be part of a complex regulatory network governing physiology and pathology of the brain. In particular, lncRNAs have been shown to play pivotal roles in the pathog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 134 publications
0
17
0
Order By: Relevance
“…CI is a local ischemic condition characterized by decreased cerebral blood flow and vascular embolism [ 17 ]. In the ischemic state, brain tissue is insufficiently supplied with oxygen and nutrients due to restrained and reduced blood flow, which results in a series of inflammatory responses, severe oxidative stress, neuronal damage, and apoptosis [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…CI is a local ischemic condition characterized by decreased cerebral blood flow and vascular embolism [ 17 ]. In the ischemic state, brain tissue is insufficiently supplied with oxygen and nutrients due to restrained and reduced blood flow, which results in a series of inflammatory responses, severe oxidative stress, neuronal damage, and apoptosis [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the various programmed cell death pathways, 64 apoptosis accounts for a large proportion of neuronal death through brain ischemia, 65 which efficiently removes damaged cells from DNA damage or during development. 66 Apoptosis plays a pivotal role in the homeostasis of normal tissues, and researchers have recently found that lncRNAs have essential effects on regulating cell apoptosis following stroke. 67 LncRNA growth arrest-specific 5 (GAS5), a ceRNA for miR137, was upregulated and negatively correlated with miR137 expression in stroke mice and OGD/R-treated primary neurons.…”
Section: Significant Role Of Long Noncoding Rnas In Cerebral Ischemiamentioning
confidence: 99%
“… 67 It is widely accepted that various lncRNAs affect cell survival in stroke by regulating autophagy. 66 MALAT1 is one of the most significantly upregulated lncRNAs in both in vivo and in vitro models of stroke and serves as a competing endogenous RNA by sponging miR-126 to upregulate its target ULK2 under hypoxic injury based on the protective effect of autophagy. 47 Similarly, lncRNA antisense noncoding RNA in the INK4 locus (ANRIL) and lncRNA FosDT were all elevated by negatively regulating miR-127 expression 80 and interacting with REST-associated chromatin-modifying proteins separately to protect against ischemic stroke.…”
Section: Significant Role Of Long Noncoding Rnas In Cerebral Ischemiamentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, more attention has been paid to blood biomarkers that can be objectively measured in the laboratory at hyperacute phase, hoping to assist in the accurate identification of ISs. The application of fast, reliable, and inexpensive blood biomarkers as an auxiliary tool, along with CT characteristics, would provide more diagnostic information that may improve stroke identification and management, especially in atypical or hyperacute IS ( Wu et al, 2019 ; Fan et al, 2020 ; Baez et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%